Development Of E-Module Think Talk Write (TTW) With Nitro Pro As A Teaching Material On Material Biotechnology In High School - Wirawati, Fajriyah; Mahadi, Imam; Sayuti, Irda (FKIP - Universitas Riau, 2023)
The purpose of this research is to produce Think Talk Write (TTW) electronic modules with nitro pro as teaching materials on appropriate biotechnology materials so that they can be used in distance learning. Data collection was carried out in March-April 2021 with 10 class XII students at SMA 1 Lubuk Batu Jaya and SMA 2 Lubuk Batu Jaya for the 2020/2021 academic year. The development model in research is Research And Development (R&D) development which uses the ADDIE development model which consists of 5 stages of development namely Analysis, Design, Development, Implementation, Evaluation. Data collection consisted of interview sheets, material expert validation sheets, media experts, biology teachers and student response questionnaires. Results of validation by material experts 82% (very qualified), media experts 94% (very qualified) and biology teachers 91% (very qualified), recapitulation results 87% with category (very qualified) and student response questionnaire results 88% (very good ). It was concluded that the Think Talk Write (TTW) Electronic Module with Nitro Pro as a Teaching Material for Biotechnology Materials is very suitable for use in high school.